2010
DOI: 10.1007/s10886-010-9880-5
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and Floral Parts Feeding by Orange Tip Butterfly Larvae Depends on Larval Position but Not on Glucosinolate Profile or Nitrogen Level

Abstract: In an attempt to identify chemical signals governing the general flower and silique feeding behavior of larvae of the orange tip butterfly, Anthocharis cardamines (L.), we investigated feeding behavior and chemistry of two major host plants: Cardamine pratensis L. and Alliaria petiolata (Bieb.) Cavara & Grande (garlic mustard). Larvae reportedly feed mainly on flowers and siliques rather than leaves in nature, and did so when observed on the original host plants. Behavioral experiments, using detached A. petio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…The pronounced influence of the initial position on the likelihood to reach the flowers, as found for A. rosae larvae in the current study, has been also reported for A. cardamines caterpillars on detached stems of their host plants (Agerbirk et al, 2010). The pronounced influence of the initial position on the likelihood to reach the flowers, as found for A. rosae larvae in the current study, has been also reported for A. cardamines caterpillars on detached stems of their host plants (Agerbirk et al, 2010).…”
Section: Traits Influencing the Locomotion Of Larvae On Plantssupporting
confidence: 87%
See 3 more Smart Citations
“…The pronounced influence of the initial position on the likelihood to reach the flowers, as found for A. rosae larvae in the current study, has been also reported for A. cardamines caterpillars on detached stems of their host plants (Agerbirk et al, 2010). The pronounced influence of the initial position on the likelihood to reach the flowers, as found for A. rosae larvae in the current study, has been also reported for A. cardamines caterpillars on detached stems of their host plants (Agerbirk et al, 2010).…”
Section: Traits Influencing the Locomotion Of Larvae On Plantssupporting
confidence: 87%
“…The distribution of physiological and chemical plant traits may have a subordinate function in driving florivory (Agerbirk et al, 2010;Carmona et al, 2011), but these traits certainly influence the feeding pattern and performance of herbivores. Perception of plant cues and the ability of herbivores to move on the plant surface, which depends on the plant species-specific morphological structures of waxes and trichomes, seem to be superordinate traits influencing the probability of florivory.…”
Section: Fitness Consequences Of Florivory On Herbivore and On Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the animal is cryptic when small, thenfrom the arguments above-it should feed on interior leaves during initial instars (Smallegange et al 2007;Agerbirk et al 2010;Bandeili and Müller 2010). Thus, larval florivores should be later instars, should be chemically defended, and should advertise those defenses.…”
Section: Introductionmentioning
confidence: 99%